2016
DOI: 10.1123/tsp.2014-0132
|View full text |Cite
|
Sign up to set email alerts
|

Applied Sport Psychology: A Profession?

Abstract: Although the field of applied sport psychology has developed, it faces further challenges on its way toward gaining greater professional status. The following principal criteria of professionalism are proposed as a test of such status: (a) provides an important public service, (b) has a knowledge-base underpinning, (c) has organizational regulation, (d) has a distinct ethical dimension, and (e) has professional autonomy. This article undertakes to explore the nature of implications for practice and the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Indeed, numerous scholars have commented on development and training, professional services, competence, and the professionalization of sport psychologists (SPs 1 ; e.g., Fletcher & Maher, 2014;Fletcher & Wagstaff, 2009;Danish & Hale, 1981;Martin, in press;McDougall et al, 2015;Portenga et al, 2017;Sly et al, 2019;Tod et al, 2017;Wagstaff, 2019;Winter & Collins, 2016;Wylleman et al, 2009). While this domain of psychological practice is a relatively new field among the helping professions, Sport Psychology has been "emerging" for the last 50 years (see Gilmore et al, 2018).…”
mentioning
confidence: 99%
“…Indeed, numerous scholars have commented on development and training, professional services, competence, and the professionalization of sport psychologists (SPs 1 ; e.g., Fletcher & Maher, 2014;Fletcher & Wagstaff, 2009;Danish & Hale, 1981;Martin, in press;McDougall et al, 2015;Portenga et al, 2017;Sly et al, 2019;Tod et al, 2017;Wagstaff, 2019;Winter & Collins, 2016;Wylleman et al, 2009). While this domain of psychological practice is a relatively new field among the helping professions, Sport Psychology has been "emerging" for the last 50 years (see Gilmore et al, 2018).…”
mentioning
confidence: 99%
“…Despite receiving criticism from purists representing one psychological model, the counselling and psychotherapy literature has suggested that eclecticism is another legitimate approach for the various practicing psychological domains (Norcross, 1986). This flexible approach has been effectively adopted to address the diverse psychological aspects of athletic PSYCHOLOGICAL MODELS 15 performance, the various client needs (i.e., one approach being more suitable for one client than another), and the multitude of diverse contexts that sport psychologists work in (e.g., Cropley, Miles, Hanton, & Niven, 2007;Sharp, Hodge, & Danish, 2014;Symes, 2014;Winter & Collins, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Professional competencies is an issue that sport psychology is still facing as a relatively new, developing profession, with training documentation often providing insufficient preparation for trainees (Fletcher & Maher, 2013;Portenga, Aoyagi, & Cohen, 2017). Developing these competencies to produce an adequate pool of appropriately trained professionals is required for the health and development of the profession (Portenga et al, 2017;Winter & Collins, 2016). Hence, these findings should act as valuable considerations for both the trainee SPC and the governing bodies that are responsible for educating and regulating the profession.…”
Section: Discussionmentioning
confidence: 99%